STRENGTHENING GOVERNANCE IN STATE-OWNED ENTERPRISES: A CRITICAL EVALUATION OF BPI DANANTARA’S MANAGEMENT AND REFORM CHALLENGES - Yohanes Paruntungan Sitorus; Arini Nur Annisa; Khansa Anindita Belva; Farel Bryan Ursipunny (Masalah-Masalah Hukum, 2025)
The governance of State-Owned Enterprises (SOEs) in Indonesia faces significant challenges, particularly regarding the independence of management, the separation of powers between regulators and operators, and political interference. This study examines the governance issues within BPI Danantara, a newly established national investment institution tasked with managing a range of strategic SOEs. Despite its potential to optimize state asset management, BPI Danantara’s governance has been hindered by the continued involvement of public officials in dual roles, which undermines managerial independence. The overlapping functions of business and state interests within SOEs create ambiguity in decision-making and open the door to inefficiencies, political interference, and corruption. A key governance issue is the practice of concurrent positions, which compromises the principle of independence, a core element of good governance. This research analyzes the implications of the Indonesian Constitutional Court Decision No. 80/PUU-XVII/2019, which prohibits Deputy Ministers from holding concurrent positions in SOEs, and the limited enforcement of this decision. It highlights the need for a more robust regulatory framework for BPI Danantara to prevent political interference and ensure transparent, accountable management. The study advocates for the establishment of a specific law for BPI Danantara, including prohibiting concurrent positions and introducing an independent supervisory board. This would help safeguard managerial independence, align decision-making with long-term national interests, and enhance the institution’s role in driving economic growth. By implementing these reforms, BPI Danantara can become a model for effective SOE governance and contribute to improving Indonesia’s economic competitiveness.